Effect of Fluocinolone-N treatment on fetal liver development in White Wistar Rats - Erika KIS (Studia Universitatis Babeș-Bolyai. Biologia)
Exposure to synthetic glucocorticoids during development can result in later cardiovascular and renal disease in sheep and rats. Although prenatal glucocorticoid exposure is associated with impaired renal development, less is known about effects on the developing liver. The main objective of this study is to analyze the side effects of glucocorticoid excess when treatment is done with Fluocinolone-N ointment, to see if it has any effect on rat newborns liver which have an important role in development of fetuses. Our results demonstrate that Fluocinolone-N treatment has negative impact upon the embryologic development of liver.